Angola : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Context and outlook: Angola's recent economic developments have been positive, but softening oil revenue and limited proven oil reserves highlight the need to contain emerging fiscal deficits, preserve policy buffers, and continue diversifying the economy. Focus of consultation: Discussions focused on mitigating the main risks to the macroeconomic framework and, inter alia, policies to return to structural fiscal surpluses over the medium term, and to support economic diversification and inclusive growth, the modernization of the monetary policy framework, and financial stability. Key policy recommendations: -- Return to structural fiscal surpluses in line with the objective set forth in Angola's Sovereign Wealth Fund, by mobilizing additional nonoil tax revenue, improving the efficiency of public investment, and reducing current spending, including by phasing out the costly and regressive fuel subsidies-while mitigating the impact on the poor through well-targeted social assistance. -- Adopt an improved medium-term fiscal framework, focusing on the structural fiscal balance to limit the impact of the oil sector on the nonoil economy. -- Develop a coherent asset-liability management framework, including a well-designed stabilization fund to shield the budget from oil revenue fluctuations. -- Further improve public financial management systems to avoid, inter alia, a recurrence in the future of domestic payments arrears. -- Continue improving the business climate to boost economic development, diversification, and competitiveness. -- In transitioning over the medium-term toward an inflation targeting regime, enhance the central bank's capacity to collect and analyze high-frequency economic data, and continue de-dollarizing the economy. -- Further strengthen the financial system, by continuing to improve the transparency and accountability of banks, and enhancing bank supervision. -- Manage public guarantees transparently and with a view to minimize fiscal costs, as envisaged in the recently-approved law on public guarantees.